Nausea and vomiting in the practice of a therapist and gastroenterologist: A review - Mariia A. Livzan; Olga V. Korpacheva; Galiia R. Bikbavova; Alisa E. Romanyuk (ZAO "Consilium Medicum", 2023)
Nausea and vomiting are among the most common complaints in outpatient clinics and hospitals, while they are associated with poor quality of life. Their causes are diverse, and pathogenetic mechanisms are multifactorial. In the presented article, the pathophysiology of nausea and vomiting is examined in detail, an algorithm of sequential actions is proposed, which is based on the following stages: finding out what the patient means by nausea and vomiting; determining whether these symptoms are acute or chronic; thorough detailing of complaints; detailed collection of anamnesis; careful physical examination. The indicated sequence of actions of the doctor during the initial treatment of the patient forms the basis for a differential diagnosis and determines further examination. Special attention is paid to the treatment of nausea and vomiting, the place of dopamine receptor blockers in the relief of these painful symptoms is discussed. The search for literature containing information on relevant studies was conducted in PubMed and Google Scholar systems according to the words: nausea, vomiting, postoperative vomiting, gastroparesis, dopamine receptor blockers, domperidone.